PERBAKIN SHOOTING SCHOOL CONSUMER SATISFACTION LEVEL - Saputra, Eka Gandara; Kholik, Abdul; Arif, Muhamad (Journal of Sport Science and Tourism Activity (JOSITA), 2022)
This study aims to determine how the level of consumer satisfaction at the Shooting School Perbakin, Jakarta. The formulation of the main problem in this study is how the level of consumer satisfaction in the Perbakin Shooting School is.This research uses descriptive quantitative research method with survey method. The data collection technique used in this research is using a questionnaire. The population in this study were the consumers of the Perbakin Shooting School with an average number of 260 visitors. The sample in this study is the Perbakin Shooting School consumers totaling 150 people and sampling using non-probability sampling technique with incidental sampling technique. The instrument validation uses Product Moment Correlation while the reliability uses Cronbach's Alpha formula. Analysis of the data using percentage statistics, and the conclusions of the research on the level of consumer satisfaction at the Perbakin Shooting School on the Physical Evidence aspect of 15%, the Reliability aspect 24%, the Responsiveness aspect 19%, the Assurance aspect 17%, and the Empathy aspect 24%. Analysis of the data using percentage statistics, and the conclusions of the research on the level of consumer satisfaction at the Perbakin Shooting School on the Physical Evidence aspect of 15%, the Reliability aspect 24%, the Responsiveness aspect 19%, the Assurance aspect 17%, and the Empathy aspect 24%.